The Correlation Self-Care Management Behavior with the Life Quality of Diabetes Mellitus - Liputo, Gusti Pandi; Djamaluddin, Nurdiana; Lamangida, Nova Novianti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Diabetes mellitus (DM) is still one of the chronic diseases thath have increased significantly every year, including in several regions of Indonesia, such as Gorontalo. The impact caused by DM has the potential to reduce the life quality of the DM sufferers, so thus sustainable alternative treatments are needed to manage the DM disease with self care management behavior. This research aims to investigate the relationship between self-care management behavior and the life quality of patients with DM in the Tilongkabila public health center. The research method is quantitative with a cross-sectional design. The population of this research is all patients with DM, comprising 61 patients with the purposive sampling technique and the data analysis using Spearman’s rho test. The results show a significant correlation between self-care management behavior and life quality in patients with DM (p = 0.000). The research concludes the emergence of a significant correlation between self-care management behavior and the quality of patients with Dm under the care of the Puskesmas Tilongkabila. Morever, it is hoped that the patients with Dm can implement the self-care management behavior optimally yet consistently to achieve a better quality of life.